ANALISIS BIOMEKANIKA PADA POSTUR TUBUH OPERATOR PENGELASAN BENGKEL SEJAHTERA MANDIRI DENGAN MENGGUNAKAN METODE RULA (RAPID UPPER LIMB ASSESMENT)) - Wirabuana, Setyo Fiddin; Mustri, Pingki Avrilia Wandani; Ramadiansyah, Dony; Rini, Asih Setyo (JURNAL LOGISTICA, 2025)
This study aims to analyze the biomechanics of the risk level of work posture in welding operators using RULA (Rapid Upper Limb Assessment). The type of research was conducted quantitatively with 3 operators consisting of 2 welding operators and 1 welding helper operator. Welding operators work every day and in making orders it takes approximately 20 days to one month which is done manually. The stages in this study: collection of demographic data, data analysis using the Nordic Body Map (NBM) and photos of operator activities. Based on data processing and analysis in this study, it was concluded that: Operator 1 (Sulfian) obtained a RULA score of 5, Operator 2 (Saeroji) and Operator 3 (Lucky) obtained a RULA score of 4. Thus, it is necessary to improve the posture of operators for each welding work activity and propose a work system with an ergonomic workbench to reduce muscle fatigue.